Green Education and Environmental Literacy in Denmark - Rasmus Lindholm (Tamilis Synex: Multidimensional Collaboration, 2025)
Green education has become a strategic approach for fostering environmental literacy and supporting sustainable development in contemporary education systems. Denmark is widely recognized as one of the leading countries in integrating sustainability principles into educational policies, school culture, and community participation. This study aims to examine how green education contributes to the development of environmental literacy in Denmark by synthesizing current literature, policy documents, and empirical studies. Using a qualitative literature review approach, this study analyzes publications from international journals, reports from international organizations, and Danish educational policies related to environmental education and sustainability. The findings indicate that Denmark promotes environmental literacy through interdisciplinary curricula, experiential learning, outdoor education, eco-school initiatives, and strong collaboration among schools, local communities, and governmental institutions. These educational practices not only improve students' environmental knowledge but also strengthen ecological awareness, critical thinking, pro-environmental attitudes, and sustainable behaviors. The study concludes that Denmark's green education model provides valuable insights for other countries seeking to strengthen environmental literacy through comprehensive educational reforms that integrate sustainability into teaching, learning, and institutional governance.